2022
DOI: 10.1371/journal.ppat.1010511
|View full text |Cite
|
Sign up to set email alerts
|

VlsE, the nexus for antigenic variation of the Lyme disease spirochete, also mediates early bacterial attachment to the host microvasculature under shear force

Abstract: Hematogenous dissemination is a critical step in the evolution of local infection to systemic disease. The Lyme disease (LD) spirochete, which efficiently disseminates to multiple tissues, has provided a model for this process, in particular for the key early event of pathogen adhesion to the host vasculature. This occurs under shear force mediated by interactions between bacterial adhesins and mammalian cell-surface proteins or extracellular matrix (ECM). Using real-time intravital imaging of the Lyme spiroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…In addition, extrapolation of our results in the knee joint microvasculature to other dissemination sites requires experimental testing due to the existence of organotypic vasculature ( 49 ), which may impose a requirement for different pathogen proteins for extravasation at different sites. Nonetheless, our model is the only experimental system in which to study the mechanistic properties of spirochete transmigration during animal infection and has resulted in unique insights into the tissue colonization process by B. burgdorferi ( 11 14 , 16 , 21 , 31 , 46 , 48 ), including the demonstration of a role for the adhesins P66 and OspC in vascular transmigration and the discovery that distinct stages of the extravasation process could be temporally separated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, extrapolation of our results in the knee joint microvasculature to other dissemination sites requires experimental testing due to the existence of organotypic vasculature ( 49 ), which may impose a requirement for different pathogen proteins for extravasation at different sites. Nonetheless, our model is the only experimental system in which to study the mechanistic properties of spirochete transmigration during animal infection and has resulted in unique insights into the tissue colonization process by B. burgdorferi ( 11 14 , 16 , 21 , 31 , 46 , 48 ), including the demonstration of a role for the adhesins P66 and OspC in vascular transmigration and the discovery that distinct stages of the extravasation process could be temporally separated.…”
Section: Discussionmentioning
confidence: 99%
“…The steps at which five B. burgdorferi adhesins function are shown. The adhesins BBK32 ( 13 , 14 , 57 , 58 ) and VlsE ( 21 ) contain potent adhesive properties that mediate early interactions between the vascular endothelium and B. burgdorferi spirochetes. Subsequently, three adhesins whose functional absence blocks vascular escape (P66 [ 30 ], DbpA/B [see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BBK32 and P66 borrelial proteins are key players mediating the stabilizing interactions and the adhesion to the cells lining the vascular lumen [ 103 , 224 , 225 ]. Recently, it was suggested that VlsE also promotes transient binding to the vasculature under flow via binding to dermatan sulphate and that a complex temporal choreography of P66, DbpA/B and OspC is required for the escape process from postcapillary venules [ 226 , 227 ]. Blood circulation is not the only mechanical stress that B. burgdorferi needs to overcome in order to infect the target tissues.…”
Section: Pathogenic Mechanisms At the Host–pathogen Interfacementioning
confidence: 99%